P780 Medical treatment and surgery in patients with elderly-onset inflammatory bowel disease: 3-year follow-up of Epi-IBD 2010–2011 cohorts. (25th January 2019) - Hernandez, V; Martinez-Cadilla, J; Langholz, E; Christodoulou, D; Turcan, S; Valpiani, D; Lakatos, P L; Vegh, Z; Goldis, A; Belousova, E; Ladefoged, K; Kiudelis, G; et al.
Abstract: Background: Previous reports have indicated that the treatment of patients with elderly-onset inflammatory bowel disease (IBD), defined as patients diagnosed ≥60 years, differs from that of younger patients. We aimed to assess the treatment of elderly-onset IBD during the first 3 years of follow-up, compared with IBD diagnosed in patients aged 15–39 and 40–59, in a European population-based inception cohort. Methods: The EPI-IBD cohort is a prospective, population-based inception cohort of patients diagnosed 2010 and 2011 in 36 European and 1 Australian centres. For this study, data regarding disease characteristics and medical or surgical treatment during the first 3 years from diagnosis were analysed. All data were entered in a secure web-based database, www.epicom-ecco.eu . Patients were classified according to age at diagnosis into 15–39y, 40–59y and ≥60y. Medical treatment was assessed in each group and the time to biological and surgical treatment was analysed by Kaplan-Meyer curves. A Cox regression model was built to assess the influence of age at diagnosis in the need of biological treatment or surgery. Results: In total, 2000 IBD patients (53.6% males) were included in the cohort, 747 (37.4%) CD, 1106 (55.3%) UC and 147 (7.4%) IBDU. Elderly-onset patients were more frequently diagnosed with UC compared with patients diagnosed at age 40–59y or 15–39y (62.9% vs. 56.3% vs. 52.6%, respectively, p = 0.006). In UC, the frequency of proctitis at diagnosis was lower, although non-statistically significant (16.2% vs. 24% vs. 23.2%, respectively, p = 0.087). In CD, elderly-onset patients more often had colonic location (38.1% vs. 29.0% vs. 22.6%, respectively, p = 0.022), while no differences were observed in disease behaviour. Elderly-onset patients were less frequently treated than the other age groups with immunomodulators (19.6% vs. 31.4% vs. 40.5%, respectively, p < 0.001) and biologicals (3.6% vs. 10.6% vs. 15.5%, respectively, p < 0.01). Biologicals were less prescribed in elderly-onset patients in both CD (7% vs. 20.9% vs. 25%, respectively, p < 0.001) and UC (2.4% vs. 5.1% vs. 9.5%, respectively, p = 0.001). No difference was found in the need of surgery among the age groups (7.7% vs. 9.7% vs. 9.1%, respectively, p = 0.617). Conclusions: In this large population-based inception cohort, elderly-onset IBD patients were less aggressively treated than younger patients. This finding may reflect a less severe disease course in elderly-onset IBD.